Relating Theology and Religious Studies: Reflections on the German Academic Landscape - Hafner, Johann Ev. (Toronto journal of theology, 2015)
The ongoing decrease of membership and influence of the mainline Christian churches in Germany provokes the question of whether Christian theological departments should continue to have a predominant position at state universities guaranteed by the constitution and state-church treaties. This situation is exacerbated when universities refuse to hire competent candidates for theological departments because they lack the required denominational profile. Further, there is a widening gap in student numbers between denominationally driven theological departments, and religious studies departments that also cover non-Christian religions, despite the fact that they share methodologies and theories, especially in philological and historical research. So this article tries to describe the relation between the disciplines of theology and religious studies in a more complex way. It uses a system-theoretical approach to show that theology addresses the problem of self-application, which religious studies cannot solve alone. Why do religious studies focus on religious studies? It argues that the discipline of theology can be integrated into religious studies departments.